The Effect of the Uyghur Issue in Türkiye-China Relations - Alperen, Ümit (Fırat University, 2024)
The Uyghur issue has an immense impact on how Türkiye and China relate to one another, view one another, interact, and worsen their relationship. China regards the Uyghur issue through the contexts of separatism, terrorism, and radicalism in terms of sovereignty and territorial integrity, whereas Turkey interprets the Uyghurs as a human rights concern due to their ties to other ethnic, cultural, religious, and historical groups. According to this paradigm, China's approach to the Uyghur issue is determined by its periodically evaluated global, regional, and internal threat levels. Furthermore, Türkiye’s position on the Uyghur issue appears to have been developed more by acting and reacting within the constraints of China’s Uyghur policy. As a result, Türkiye’s responses to tensions over the Uyghur problem may have an impact on bilateral ties. Türkiye’s Uyghur policy appears to have altered as a result of recent inequalities in its political and economic relationship with China. According to this study, the Uyghur question has substantially affected the relationship between Türkiye-China and will continue to do so. This essay examines the influence of the Uyghur question on Turkish-Chinese relations in light of cyclical conjunctural changes.

Uygur sorunu, Türkiye ve Çin ilişkilerinin şekillenmesinde, tarafların birbirlerini algılamasında, etkileşim düzeylerinin artmasında, azalmasında ve ilişkilerinin kötüleşmesinde önemli rol oynamaktadır. Türkiye, Uygurlarla etnik, kültürel, dini ve tarihsel bağları nedeniyle insan hakları bağlamında ilgilendiğini belirtirken, Çin ise Uygur sorununu egemenlik ve toprak bütünlüğü meselesi bağlamında ayrılıkçılık, terörizm ve radikalizm kapsamında değerlendirmektedir. Bu çerçevede Çin’in Uygur sorununa yaklaşımı küresel ve bölgesel düzeyde dönemsel olarak algıladığı tehdit düzeyine göre şekillendiği görülmektedir. Türkiye’nin Uygur sorununa yaklaşımı ise Pekin’in Uygurlara yönelik politikaları çerçevesinde daha çok etki ve tepki bağlamında şekillendiği görülmektedir. Dolayısıyla Uygur sorunundaki gerilimlere Türkiye’nin gösterdiği reaksiyonlar ikili ilişkileri de doğrudan etkileyebilmektedir. Son yıllarda Türkiye-Çin ilişkilerinin ekonomik ve politik olarak asimetrikleşmesinin de bir neticesi olarak Türkiye’nin bu reaksiyoner Uygur politikasının konjonktürel bir değişim geçirdiği görülmektedir. Bu çalışma, Uygur sorununun Türkiye-Çin ilişkilerini şekillenmesinde, tarafların birbirini algılamasında sürekli bir etkisinin olduğunu ve olacağını savunmaktadır. Bu makale, Uygur sorununun dönemsel olarak konjonktürel değişimler çerçevesinde Türkiye-Çin ilişkilerini nasıl etkilediğini incelemektedir.
UYGUR SORUNUNUN TÜRKİYE-ÇİN İLİŞKİLERİNE ETKİSİ
Keywords: Cultural Studies of Nation and Region; Ulus ve Bölgenin Kültürel Çalışmaları